2014
DOI: 10.1038/ncomms6852
|View full text |Cite
|
Sign up to set email alerts
|

The Wilms’ tumour suppressor Wt1 is a major regulator of tumour angiogenesis and progression

Abstract: Angiogenesis, activation of metastasis and avoidance of immune destruction are important for cancer progression. These biological capabilities are, apart from cancer cells, mediated by different cell types, including endothelial, haematopoietic progenitor and myeloid-derived suppressor cells. We show here that all these cell types frequently express the Wilms' tumour suppressor Wt1, which transcriptionally controls expression of Pecam-1 (CD31) and c-kit (CD117). Inducible conditional knockout of Wt1 in endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 65 publications
6
88
0
Order By: Relevance
“…The angiogenic role of WT1 is supported by a reduced sprouting capacity in an aortic ring angiogenesis assay from mice lacking WT1 expression in endothelial cells. In addition, the same study revealed that the vessel density in matrigel plugs after subcutaneously injection, in mice lacking WT1 expression in endothelial cells, is significantly reduced compared to wild-type animals (71). Furthermore, deletion of WT1 in endothelial cells resulted in major reduction in cardiac vessel formation during mouse cardiac development supporting the presence of WT1 and the essential role of WT in cardiac endothelial cells (86).…”
Section: The Role Of Wt1 In Endothelial Cellsmentioning
confidence: 67%
See 1 more Smart Citation
“…The angiogenic role of WT1 is supported by a reduced sprouting capacity in an aortic ring angiogenesis assay from mice lacking WT1 expression in endothelial cells. In addition, the same study revealed that the vessel density in matrigel plugs after subcutaneously injection, in mice lacking WT1 expression in endothelial cells, is significantly reduced compared to wild-type animals (71). Furthermore, deletion of WT1 in endothelial cells resulted in major reduction in cardiac vessel formation during mouse cardiac development supporting the presence of WT1 and the essential role of WT in cardiac endothelial cells (86).…”
Section: The Role Of Wt1 In Endothelial Cellsmentioning
confidence: 67%
“…Although the expression of WT1 in cardiac endothelial cells is unique during normal conditions, the expression is also present in endothelial cells in other organs in a pathological condition. WT1 is found in endothelial cells of the skin in patients with chronic dermatitis (69), and WT1 has been observed in endothelial cells in a wide variety of tumors (68)(69)(70)(71)(72).…”
Section: The Role Of Wt1 In Endothelial Cellsmentioning
confidence: 99%
“…Furthermore, a Wt1-GFP transgene is expressed in a population of visceral CD34 + Sca1 + stromal vascular fraction that are enriched for adipogenic progenitors suggesting Wt1 might also function in visceral adipocyte development [79]. Wt1 precursors are multipotent, generating testicles, ovaries, kidneys, spleen, adrenal glands, the mesothelial layer of visceral organs, and endothelial cells [79, 80]. Thus, a lineage marker that specifically labels all visceral white adipocytes has not been identified.…”
Section: Tissue Resident Adipocyte Progenitorsmentioning
confidence: 99%
“…To prove that coronary vascular defects in G2-Gata4 Cre ;Wt1 LoxP/LoxP mutants are not caused by disrupted epicardial signaling, we crossed Tie2 CreERT2 (18) and Wt1 LoxP/LoxP mice to create endothelial cell-specific Wt1 knockouts (19). Tamoxifen was injected at E10; the specificity of tamoxifen-induced recombination is shown in Fig.…”
Section: G2-gata4mentioning
confidence: 99%